The impact of disability, fatigue and sleep quality on the quality of life in multiple sclerosis - Ghaem Haleh; Haghighi Afshin (Annals of Indian Academy of Neurology, 2008)
Background: Only few papers have investigated the impact of multiple sclerosis (MS), especially MS-related fatigue and the impact of the quality of sleep on the quality of life (QoL) in MS patients. Objective: The objective of this study was to measure the quality of life in MS patients and the impact of disability, fatigue and sleep quality, using statistical modeling. Materials and Methods: A cross-sectional study was conducted and data was collected from 141 MS patients, who were referred to the Mottahari Clinic, Shiraz, Iran, in 2005. Data on health-related quality of life (MSQoL-54), fatigue severity scale (FSS), and Pittsburgh sleep quality Index (PSQI) were obtained in the case of all the patients. Epidemiology data concerning MS type, MS functional system score, expanded disability status scale (EDSS) etc. were also provided by a qualified neurologist. Spearman a coefficient, Mann-Whitney U test, and linear regression model were used to analyze the data. Results : The mean ±SD age of 141 MS patients was 32.6±9.6 year. Thirty five (24.8%) of them were male and the others were female. Eighty two (58.1%) of the patients had EDSS score of ≤ 2, 36 (25.5%) between 2.5 and 4.5, and 23 (16.3%) ≥ 5. As per PSQI scores, two (1.4%) of the patients had good sleep, 16 (11.3%) had moderate sleep and 123 (87.2%) had poor sleep. There was a significant high positive correlation between the quality of mental and physical health composite scores (r = 0.791, P < 0.001). There was a significant negative correlation between the quality of physical score and age (r = -0.88, P < 0.001), fatigue score (r = -0.640, P < 0.001), EDSS score (r = -0.476, P < 0.001) and PSQI (sleep quality r = -0.514, P < 0.000). Linear regression analysis showed that PSQI score, EDSS, and fatigue score were predictors in the model between the quality of physical score and covariates ( P < 0.001). Linear regression model showed that fatigue score and PSQI were predictors in the model between the quality of mental score and covariates ( P < 0.001). Discussion and Conclusion: In conclusion, it may be said that MS patients had poor and moderate quality of mental and physical health. The quality of life was impaired as seen by PSQI, EDSS, and FSS. It is our suggestion that these patients require the attention of health care professionals, to be observed for the need of possible psychological support.